Effects of a Novel Dental Gel on Plaque and Gingivitis: A Comparative Study - Dadkhah, M (Dentistry (Sunnyvale), 2014)
OBJECTIVES: The goal of this prospective, randomized, controlled, double-blinded study was to evaluate the effects of a novel dental gel on plaque and gingival health. The dental gel was designed to (1) break up and prevent re-accumulation of microbial biofilm, and (2) inhibit metal mediated inflammation. MATERIALS AND METHODS: Twenty-five subjects with moderate gingival inflammation (Löe and Silness Gingival Index ≥2) and pocket depths <4 were randomly assigned to brush twice daily for 21 days with the test or the control dental gel. On Days 0, 7, 14 and 21, plaque levels (Quigley-Hein, Turesky Modification Plaque Index), gingival inflammation (Löe and Silness Gingival Index) and gingival bleeding (modified Sulcus Bleeding Index) were determined by one blinded, investigator using a pressure sensitive probe. RESULTS: After 3 weeks, all 3 clinical indices were significantly improved in both groups (P<0.05) and significantly lower in the test group (P<0.05). CONCLUSION: The novel dental gel formulation was provided effective plaque control and reduced gingival inflammation. CLINICAL RELEVANCE: A novel dentifrice formulation may be an effective tool for plaque removal and maintaining gingival health.